Development of Yellow Discoloration in Sawai (Pangasianodon hypophthalmus) Muscle due to Lipid Oxidation - Chodsana Sriket; Phanat Kittiphattanabawon; Umesh Patil; Soottawat Benjakul; Theeraphol Senphan; Sitthipong Nalinanon (Preventive Nutrition and Food Science, 2023)
* values), and pyrrole compounds increased when Sawai liposomes and microsomes were oxidized using iron and ascorbate. Meanwhile, the levels of free amines decreased, particularly as the iron content (25∼100 μM) and incubation time (0∼20 h) increased. The impact of oxidized liposomes at different levels (1, 2, and 5%) on the salt-soluble Sawai myofibrillar proteins was also evaluated. The findings revealed that lipid oxidation products reduced the sulfhydryl content and increased the surface hydrophobicity and carbonyl content of the salt-soluble Sawai myofibrillar proteins. These results imply that the formation of yellow discoloration in Sawai muscle could be due to nonenzymatic browning reactions occurring between lipid oxidation products and amines in the muscle protein.
Keywords: Meat and Animal Product Quality; Biochemical effects in animals; Adipose Tissue and Metabolism